EFEKTIVITAS PENGGUNAAN E-BOOK UNTUK MENGEMBANGKAN KEMAMPUAN LITERASI ANAK USIA 4-5 TAHUN DI TK CUT MEUTIA BANDA ACEH - Fitri , Aida; Sabaruddin, Sabaruddin; Nuraida; Meutiawati, Ida (LIBRIA, 2026)
This study is motivated by literacy problems among children aged 4–5 years at TK Cut Meutia Banda Aceh, such as difficulties in recognizing letter symbols, connecting vocabulary, arranging words, and pronouncing syllables and images. This study aims to test the effectiveness of using e-books as an interactive digital medium in developing children's literacy skills. The research method used is a quantitative approach with a pre-experimental type using a one-group pretest-posttest design. The research sample was selected using a simple random sampling technique, namely class A2, which consisted of 21 children. The data collection instruments used included observation sheets and documentation. The data analysis techniques applied consisted of normality tests, t-tests, and hypothesis testing. The results showed a significant increase in children's literacy skills after the treatment. This is evidenced by the increase in the average pretest score from 1.5 to 3.5 in the posttest. In addition, the results of the hypothesis test showed that the value of  (45.04) >  (1.724), so   is accepted and  is rejected. Thus, it can be concluded that the use of e-books is effective for developing the literacy skills of children aged 4–5 years at TK Cut Meutia Banda Aceh